The lunar photoelectron sheath: A change in trapping efficiency during a solar storm. Issue 5 (30th May 2013) - Farrell, W. M.; Poppe, A. R.; Zimmerman, M. I.; Halekas, J. S.; Delory, G. T.; Killen, R. M.
Abstract : [1] On the lunar dayside, photoelectrons are quasi‐constantly emitted from the Moon's surface and this electron flux acts to typically charge the dayside lunar surface a few volts positive. In arriving at an equilibrium surface potential, the surface will charge to balance the two primary currents: the outgoing photoelectron flux, Jp, against the incoming solar wind electron thermal flux, Je . In nominal solar wind conditions, Jp > Je and the surface charges positive, trapping most of the photoelectrons. However, during the passage of a coronal mass ejection (CME), the incoming electron thermal flux, Je, will quickly change from being less than Jp to being greater than Jp on time scales of 1–2% of a lunation. Using a set of independently developed particle‐in‐cell plasma codes, we find at times when Jp / Je < 1, there is substantially less near‐surface electrostatic trapping of the photoelectrons due to the reduction of the restraining surface potential. The photoelectron population then has almost direct access to upstream regions. We find that the morphology of the sheath is very different in the CME's dense cool plasma than in the nominal solar wind, with a larger relative portion of the photoelectrons now liberated to propagate upstream into plasma regions ahead of the Moon. Key Points: Dayside of Moon‐emitted photoelectrons These are usually trapped near surface During a solar storm, the photoelectrons can escape upstream